Relative gene expression for genes and virulence factors formation of biofilms of Streptococcus mutans bacteria using polymerase chain reaction in real-time (RT-PCR) - A. J. Al-Kaaby, Wafaa; H. Al-Hamadani, Adnan; K. A. Al-Shebli, Majed (Al-Qadisiyah Journal of Pure Science, 2018)
A total of 479 bacterial isolates were collect from 409 swabs from the teeth surfaces teeth and gingiva of the auditors admitted to the centers specialist and dental clinics in Al-Diwaniya city for different ages by specialist doctor on period from 1/11/2012 AC till 1/3/2013 AC. Bacterial isolates diagnosed by Vitek compact 2 system to positive and negative gram stain head it Streptococcus spp. by highest percentage of 31.52%, followed by Staphylococcus spp. by 20.45% and Lactobacillus spp. by 12.52% and Candida spp. by 10.64%, and follow then some germs that made ​​a few percentages compared to the bacteria mentioned, also S. mutans obtain among microbial species isolated from teeth surfaces and gingiva frequency highest in the number of isolates (56 isolate) and tested their on biofilm formations; then 44 isolation (44.64%) high formations, 16 isolation (28.57%) medium formations and 15 isolation (26.79%) non biofilm formations. The impact of carbohydrates appear apparent on S. mutans isolates in biofilm formations on bio-growth medium; then amounted to the presence of sucrose 35.71%, followed by glucose with fructose together in the medium (25.00%) then glucose (16.07%) and fructose (12.50%).Quantitative real time – polymerase chain reaction (qRT-PCR) using based on two sides, the first: it is counting the absolute levels of mRNA in conservative gene (16s rRNA) to S. mutans and comparing it with the virulence factors genes (spaP, gbpB and gtfB) and biofilm genes (luxS and brpA) to those germ and the second: is the relative count which gene expression represents of virulence genes and biofilm S. mutans, and the test proved as follows: A significant decrease in relative count gene expression levels of genes virulence factors (spaP and gbpB), except gene gtfB which showed significant differences between the transactions at the probability level P ≥ 0.05. A significant decrease in relative count gene expression levels of genes biofilm (luxS and brpA) at the probability level P ≥ 0.05.